A Study On The Impact Of Training And Development To Improve The Performance Of Employees Of Construction Industry In Pune City (International Journal of Food and Nutritional Sciences, 2022)
The researcher's goal was to investigate how training has shaped society in various ways since the beginning of time. It serves as a vehicle for passing on various skills from one generation to the next. However, as time has passed, training intensity has changed drastically. Numerous training approaches and strategies have emerged as a result of technological advancement. These modifications have altered the need for training and given it new dimensions. Both global and micro levels of human resource development are implemented. At a macro level, training is essential for raising social issue awareness among the populace, educating individuals, and promoting literacy in society to enable people to live better lives. The goal of training activities at the micro-level is to help employees in an organisation become more competent at their jobs and improve their performance in order to advance the organisation. So, everybody attends training. It is a well-known fact that an organization's performance depends on the calibre of its people resource in addition to finances, resources, and equipment.